Penerapan Sistem Absensi Guru Menggunakan QR Code Di MI Miftahul Huda - Syarah; Hendri Ardiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Attendance attendance also includes an important role in every educational institution. Where attendance is one of the main roles that can support and support every activity carried out in educational institutions. Like the absence of teachers and employees at MI Miftahul Huda Sawah which still uses the manual method (signature), this method is very vulnerable for an educational institution because of the level of discipline that cannot be controlled and can be misused by irresponsible people, other losses that may appears in the manual attendance system is data recapitulation which still takes a lot of time and effort. The purpose of this study is to implement an attendance system that makes it easier for teachers to process attendance at school, also in preparing monthly reports or recapitulations for teachers and employees made easy by having an attendance system built. This attendance system uses the QrCode framework and technology. As well as using the codeigniter framework with the programming language PHP and HTML and MySQL as the database, it also uses the waterfall method.